Evaluation of Filgrastim Therapy in Kidney Transplant Recipients. (December 2017) - Poon, Teresa; Guerra, Christina M.
Context: Neutropenia is associated with a high risk of serious infections in kidney transplant recipients. There are no sufficient studies of using granulocyte colony-stimulating factors, such as filgrastim, in renal transplant recipients to establish a clear, specified role of this off-label indication. Using filgrastim in these patients may increase the risk of rejection by overstimulating the immune system. Objective: To evaluate the use of filgrastim in adult kidney transplant recipients presenting with neutropenia. Patients and Design: Data were obtained from a medication utilization report of filgrastim in kidney transplant recipients at our center from September 2012 to August 2015. Main Outcome Measure(s) and Results: There were 28 cases of neutropenia that were treated with a range of 1 to 5 doses of filgrastim 300 or 480 μg, with a mean of 1.79 doses. The mean total dose of filgrastim administered per episode of neutropenia was 632 μg (8.6 μg/kg). Overall, 87.5% of the cases achieved a white blood cell count of at least 3 × 10 9 cells/L within 7 days of hospital discharge. There were no cases of infection or acute rejection following treatment. Conclusions: The use of filgrastim in kidney transplant recipients demonstrated success in reversing neutropenia. Short courses of therapy were required with minimal adverse events. Patients who required readmission were successfully re-treated. Additional studies are required to determine the most effective dose and duration of treatment.